The New Superconductors - Owens, Frank J. (Selected Topics in Superconductivity, 2002)
In The New Superconductors, Frank J. Owens and Charles P. Poole, Jr., offer a descriptive, non-mathematical presentation of the latest superconductors and their properties for the non-specialist. Highlights of this up-to-date text include chapters on superfluidity, the latest copper oxide types, fullerenes, and prospects for future research. The book also features many examples of commercial applications; an extensive glossary that defines superconductivity terms in clear language; and a supplementary list of readings for the interested lay reader.